Effect of Solvent Evaporation Time and Casting Thickness on the Separation Performance of Cellulose Acetate Butyrate Blend Membrane - Manimaran, Darvin; Jawad, Zeinab Abbas; Thiam Leng, Chew (Journal of Applied Membrane Science & Technology, 2019)
Global warming and climate change due to greenhouse gases (GHGs) emission, mostly carbon dioxide (CO2), have induced global efforts to minimize the concentration of atmospheric CO2. To reduce the effects of this problem, membrane technology is selected for the separation of CO2 due to the energy efficiency and economic advantages exhibited. In this study, the chosen polymeric material, cellulose acetate butyrate (CAB) is optimized using a wet phase inversion method with various molecular weight and different casting conditions due to its outstanding film-forming specifications and capabilities of fabricating a defect-free layer of neat membrane. The membrane was synthesized by blending three different molecular weights (Mn) of 12,000, 30,000 and 70,000 at different casting thickness, 150 µm to 300 µm and solvent evaporation time of 3.5 to 5 min. The results of these predominant parameters were then utilized to determine a high performance CAB membrane suitable for an enhanced CO2/Nitrogen (N2) separation. Eventually, a high separation performance CAB membrane was successfully synthesized with a CO2/N2 selectivity of 1.5819 ± 0.0775 when the solvent evaporation time and casting thickness was optimized at 4.5 min and 300 µm, respectively. Through this study, an improved understanding between membrane casting conditions and membrane performance has been achieved, for future development and progress.